Youth employability and skills development - Park, Young-bum [Herausgeber] (My University, 2013)
"On October 9, 2012, in celebrating the 15th anniversary the Korea Research Institute for Vocational Education and Training held an international seminar on 'Youth Employability and Skills Development' aimed at supporting participating countries to make progress in resolving youth unemployment through sharing of policy experiences in tackling youth unemployment." This book includes the papers presented at the international seminar with an introductory chapter. The papers regard the current situation of youth unemployment in seven countries (Korea, Japan, Taiwan, China, United States, United Kingdom, Germany) and deal with the following questions: What is the situation of youth employment and unemployment? What are the causes for the youth unemployment? Which measures are undertaken to combat youth unemployment (VET related policies as well as other policy measures)? (Hrsg., BIBB-Doku)
Keywords: P 1.1 Jugendliche; G 1.2.2.4 Arbeitslosigkeit; I 2.1 Deutschland; I 2.3.4 Asien; I 2.3.2 Nordamerika; I 2.2.1 Westeuropa; Jugendarbeitslosigkeit; Beschäftigungsfähigkeit; Berufsausbildung; Beziehung Bildungssystem Beschäftigungssystem; Internationaler Vergleich; Bundesrepublik Deutschland; Südkorea; Japan; Taiwan; China; USA; Vereinigtes Königreich